Adult education and growth - Dieter Dohmen; Galiya Yelubayeva (Forschungsinstitut für Bildungs- und Sozialökonomie (FiBS), 2019)
The paper presents an appraisal of theoretical links between adult education (human capital in general) and macroeconomic growth and provides a summary of the findings in the main empirical macro-studies for European countries. An initial analysis of broad statistics for all EU member states suggests a correlation between investments in adult education (human resources), the working environment and growth, however, clear causal relationships are difficult to establish. The paper provides a broad historical survey of empirical macro-studies following the theory of human capital growth. This paper aims to answer the following research questions: (1) What are the various historical antecedents and early conceptualisations of the human capital theory that are useful in understanding the impact of education on economic growth? (2) What is current state of research that measures this impact econometrically? (3) What is the impact of human capital (determined as adult education) to economic growth? (4) How to consolidate these findings in a systematic way that builds on the theoretical basis of human capital (adult education) theory?
Keywords: 330